Does the Broad Public Want to Consolidate Public Debt? – The Role of Fairness and of Policy Credibility - Helmut Stix (Oesterreichische Nationalbank (OeNB), 2011)
The paper tests selected long-standing hypotheses about why voters support or oppose fiscal consolidation. Deviating from most of the empirical literature which mainly focuses on cross-sectional and time series evidence, this paper employs data from a public opinion survey that has been conducted in spring 2010 in Austria. The results show (i) that voters are fiscally prudent, that (ii) they behave rationally in the sense that self-interest matters, that (iii) they care for the next generation (this effect is surprisingly small), that (iv) the distributional fairness among the current generation is as at least as important as the intergenerational aspect and that (v) the low credibility of medium-term fiscal policy plans can be a serious impediment to voters' support for consolidation. These results bear direct implications on the design of fiscal consolidation plans.
Keywords: H63; H31; D12; 330; Public debt; fiscal adjustment; political economy; fairness; credibility